Principal Management In Improving Teacher Competence Through The Learning Process - Tubagus Asyananda Pranoto Utomo (JOSSE: Journal of Social Science and Economics, 2022)
The context of this research is an effort to increase teacher competence through the learning process because of the intense competition between schools to get students and the community, which incidentally prefers institutions that can help students to be able to go straight into the world of work. The purpose of the research is to describe how the school principal's management improves teacher competency through the learning process at Integral Islamic Elementary School Lukman AL-Hakim Situbondo. The type of research used is qualitative research with a case study approach. Data collection techniques by way of observation, interviews, and documentation. The data analysis technique used in this qualitative research has four stages, namely data collection, data reduction, data presentation, drawing conclusions and suggestions. Whereas in looking for the validity or validity of the data using data triangulation techniques. The results of this study are (1) The management carried out by the principal in improving teacher competence is as follows: (a) Include teachers in training, training and seminars (b) Prioritize discipline. (c) Teacher motivation (d) Supervision conducted every semester. (2) Carrying out the main tasks while still carrying out additional tasks such as religious activities and also always making teaching equipment. (3) Supporting factors